2018
DOI: 10.1155/2018/1942451
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of In Vitro Cyto- and Genotoxicity of Barbatimão Extract on Human Keratinocytes and Fibroblasts

Abstract: Barbatimão (Stryphnodendron adstringens, Mart.) is a native Brazilian species used in traditional medicine and some commercial preparations owing to its strong wound-healing activity. However, controversy regarding its use due to safety concerns over the potential genotoxic effect of this plant remains. In order to clarify this issue, the effect of hydroalcoholic extract of barbatimão in vitro on cell viability, DNA damage, and induction of apoptosis in two commercial cell lines of keratinocytes (HaCaT) and fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The effect of the S. adstringens hydroalcoholic extract has also been evaluated for cell viability, DNA damage, and apoptosis induction in keratinocytes (HaCaT), and fibroblast (HFF-1) cell lines. The results have suggested that the extract may have a genoprotective and anti-apoptotic effects for human keratinocytes and fibroblasts (Pellenz et al, 2018).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The effect of the S. adstringens hydroalcoholic extract has also been evaluated for cell viability, DNA damage, and apoptosis induction in keratinocytes (HaCaT), and fibroblast (HFF-1) cell lines. The results have suggested that the extract may have a genoprotective and anti-apoptotic effects for human keratinocytes and fibroblasts (Pellenz et al, 2018).…”
Section: Discussionmentioning
confidence: 97%
“…Genotoxicity tests demonstrate effects on DNA, gene mutations, and chromosomal aberrations. Some studies have shown that S. adstringens maintains cell viability when analyzed on mammalian cell culture (de Oliveira et al, 2013;Henriques et al, 2016;Ishida et al, 2006), and has a protective effect on cellular genetic material (Costa et al, 2010;Pellenz et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…47 It was proven that Gallic acid effectively promoted wound healing with the activation of c-Jun N-terminal kinases (JNK), focal adhesion kinases (FAK), and extracellular signal-regulated kinases (Erk), increased fibroblast and keratinocyte proliferation as well as migration and decreased apoptosis in the keratinocyte and fibroblast cells. 48 Treatment with Gallic acid also helps to accelerate wound contraction, increases hydroxyproline content in the granulation tissues, helps to provide high tensile strength, increases collagen synthesis and deposition, and increases the vascularization process with decreased IL-6, NO, and TNF-α levels. 49 Besides increased fibroblast activity, a decrease in inflammation is the most crucial contribution of Gallic acid in wound healing.…”
Section: Mmp-9mentioning
confidence: 99%
“…Research, Society and Development, v. 10, n. 1, e3010111350, 2021 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i1.11350 Hernandes et al, 2010, investigated the healing effect of back in wounds made in the skin of rats, after of treatment in which the existence of the stimulated proliferation of the keratinocytes (Hernandes et al, 2010). Other study evaluated the modulation of genotoxicity and apoptosis of the Barbatimão extract on DNA damage in human keratinocytes and dermal fibroblast and identified genoprotective effect on cells by decreasing the levels of DNA oxidation and reactive oxygen species (ROS) levels (Pellenz et al, 2018).…”
Section: Healing Potential Of Stryphnodendron Adstringensmentioning
confidence: 99%
“…Since 2002, the use of phytotherapeutics medical has been considered a part of healthcare due to its potential for the development of new drugs according with World Health Organization (WHO) (Goes et al, 2020;Moraes et al, 2020;Pellenz et al, 2018;Santos et al, 2020) Stryphnodendron adstringens (Mart.) Coville (Barbatimão) is a native Brazilian species used in traditional medicine and some commercial preparations as natural product (De Santana, Voeks, & Funch, 2016).…”
Section: Introductionmentioning
confidence: 99%